Optimizing respiratory care: clinical pharmacist interventions in respiratory tract infection management at a tertiary teaching hospital - Chandrashekhar Mallikarjun Patil; Princy Domnic Dsouza; Sai Phalguna Prakash Chitralu; Vinod Ashok Koujalagi; Agadi Hiremath Viswanatha Swamy; Sanatkumar Bharamu Nyamagoud (Monaldi Archives for Chest Disease)
Respiratory tract infections (RTIs) are prevalent in India, affecting approximately 11.3% of the population. India leads globally in lung disease mortality, including chronic obstructive pulmonary disease and asthma, contributing significantly to disability-adjusted life years and mortality rates. The role of clinical pharmacist interventions (CPIs) in optimizing antibiotic use and managing RTIs is increasingly recognized as vital for improving patient outcomes and reducing healthcare costs. This study aimed to evaluate the effectiveness of CPIs in managing RTIs among inpatients at Vivekananda General Hospital, Hubballi, and to identify common drug-related problems (DRPs) using the Hepler-Strand classification system. A cross-sectional study was conducted over 6 months, including 200 inpatients diagnosed with RTIs. Data was collected through patient profiles, treatment charts, and medical case sheets. The study employed descriptive and inferential statistical analyses to evaluate the impact of CPIs on antibiotic therapy and the prevalence of DRPs. The study identified drug-drug interactions as the most frequent DRP (38.30%), followed by drug duplication (31.49%) and improper drug selection (9.79%). Other issues included adverse drug reactions (4.68%), overdosage (5.53%), untreated indications (6.38%), subtherapeutic dosage (2.13%), and drug use without indication (1.70%). CPIs, including prospective audits, prescription feedback, and healthcare professional education, effectively addressed these issues, improved antibiotic appropriateness, and optimized patient outcomes. CPIs significantly enhance the management of RTIs by addressing various DRPs and optimizing antibiotic use. The study underscores the importance of incorporating pharmacists into antimicrobial stewardship programs to improve medication safety, efficacy, and overall patient care in managing RTIs. Continued emphasis on pharmacist-led interventions and adherence to best practices in antimicrobial stewardship is essential for reducing the burden of respiratory diseases in India.